Systematic Literature Review : Peran Filsafat Ilmu Dan Pendidikan Jasmani Dalam Pembentukan Karakter - Luthfi Prasasti Putri; Zaky Haidar Firmansyah; Reza Syaef Nuralie; Aditia Putra Munggaran; Carsiwan (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Character education is a fundamental goal of education that emphasizes not only cognitive and psychomotor aspects but also moral, ethical, and social values. Physical education has strategic potential as a medium for character development through movement-based learning experiences, while the philosophy of science serves as a conceptual foundation for understanding human nature, learning processes, and educational objectives. This study aims to examine the role of the philosophy of science and physical education in shaping students’ character based on scientific literature. This research employed a Systematic Literature Review (SLR) following the PRISMA protocol. Literature searches were conducted through Google Scholar and SINTA databases covering the period from 2015 to 2025, with inclusion criteria consisting of Indonesian-language articles published in nationally accredited journals. A total of 11 articles met the selection criteria and were analyzed thematically. The findings indicate that the philosophy of science contributes to character development through ontological, epistemological, and axiological dimensions, while physical education effectively internalizes character values such as discipline, responsibility, cooperation, sportsmanship, honesty, and moral-social awareness through physical activity experiences. The integration of the philosophy of science into physical education is also increasingly relevant in addressing character degradation challenges in the digital era. Therefore, strengthening the philosophical foundation of physical education is essential for fostering holistic and sustainable character development among students.